Projected values of thermal and precipitation climate indices for the broader Carpathian region based on EURO-CORDEX simulations - Nóra Skarbit; János Unger; Tamás Gál (Hungarian Geographical Bulletin, 2022)
Since our climate is in a rapid changing phase, it is crucial to get information about the regional patterns of basic climatic parameters and indices. The EURO-CORDEX project provides high quality regional climate model outputs, but these raw datasets are not convenient for the application in wider geoscience studies. According to the authors’ knowledge, there is a lack in published spatial information about basic climate parameters and indices in Central-Europe and especially in the broader Carpathian region therefore the basic aim of this study to fill this gap. The study presents the future trends in daily air temperature and precipitation and various climatic indices in the broader Carpathian Basin region during the 21st century. The indices are calculated using multi-model average temperature and precipitation data from EURO-CORDEX model simulations for the future time periods (2021–2050, 2071–2100) and emission scenarios (RCP4.5, RCP8.5). The indices present the future trends of the heat load, energy demand as well as extreme precipitation and drought characteristics. Based on the results the temperature increase is obvious and the heat load and energy demand quantifying indices follow the temperature trend. However, the trend is difficult to evaluate in case of precipitation. The changes in the precipitation and the related indices can be considered small and appear within the regions. The future changes are the most considerable in the Carpathian Basin, but the entire examined region faces crucial changes in the following decades.